Accurate temperature dependence of structure factors of l-alanine and taurine for quantum crystallography - Mibuki Hayashi; Takashi Nishioka; Hidetaka Kasai; Eiji Nishibori (IUCrJ)
Multi-temperature high-quality structure factors of L-alanine and taurine were re-measured at the SPring-8 BL02B1 beamline for method development in quantum crystallography. The quality of the data was evaluated by comparison with previous studies. In the case of taurine, we found that the data quality was highly affected by small amounts of twinning. Residual electron density around the sulfur atoms observed in a previous study [Hibbs et al. (2003). Chem. A Eur. J. 9, 1075–1084] disappeared with the re-measured data. X-ray wavefunction refinements were carried out on these data. The difference electron density between the X-ray constrained wavefunction (XCW) results and the Hartree–Fock charge density showed a positive difference electron density around the nucleus and a negative difference electron density between the bonds. These features were consistent with those reported [Hupf et al. (2023). J. Chem. Phys. 158, 124103]. It was found that the deformation density around the nucleus and between bonds due to electron correlations and electronic polarization could be confirmed by the XCW method using the present structure factors.